hTERT Promotes CRC Proliferation and Migration by Recruiting YBX1 to Increase NRF2 Expression - Gong, Chunli; Yang, Huan; Wang, Sumin; Liu, Jiao; Li, Zhibin; Hu, Yiyang; Chen, Yang; Huang, Yu; Luo, Qiang; Wu, Yuyun; Liu, En; Xiao, Yufeng (Frontiers in Cell and Developmental Biology, 2021)
High human telomerase reverse transcriptase (hTERT) expression is related to severe Colorectal Cancer (CRC) progression and negatively related to CRC patient survival. Previous studies have revealed that hTERT can reduce cancer cellular Reactive Oxygen Species (ROS) levels and accelerate cancer progression; however, the mechanism remains poorly understood. NFE2 related factor 2 (NRF2) is a molecule that plays a significant role in regulating cellular ROS homeostasis, but whether there is a correlation between hTERT and NRF2 remains unclear. Here, we showed that hTERT increases CRC proliferation and migration by inducing NRF2 upregulation. We further found that hTERT increases NRF2 expression at both the mRNA and protein levels. Our data also revealed that hTERT primarily upregulates NRF2 by increasing NRF2 promoter activity rather than by regulating NRF2 mRNA or protein stability. Using DNA pull-down/MS analysis, we found that hTERT can recruit YBX1 to upregulate NRF2 promoter activity. We also found that hTERT/YBX1 may localize to the P2 region of the NRF2 promoter. Taken together, our results demonstrate that hTERT facilitates CRC proliferation and migration by upregulating NRF2 expression through the recruitment of the transcription factor YBX1 to activate the NRF2 promoter. These results provide a new theoretical basis for CRC treatment.